RAA-CRISPR/Cas12a-driven two-tube, one-tube and one-tube-LFS for rapid detection of feline parvovirus - Ge, Guangyu; Chen, Zhiyi; Liu, Siyuan; Tang, Zhonglin; Yin, Yulong; He, Qinghua (Frontiers in Veterinary Science, 2025)
A One-tube method biosensor was developed based on Two-tube recombinase-aid amplification (RAA)-CRISPR/Cas12a system due to the risk of aerosol contamination caused by open-tube operations in the Two-tube method. To further enable naked-eye visualization and portable detection of feline parvovirus (FPV), the lateral flow strip (LFS) technology was introduced to construct One-tube-LFS method. The limits of detection (LODs) of the One-tube and Two-tube methods were determined to be both 4.277 copies/μl, while the One-tube-LFS method was 42.77 copies/μl, which exhibited an LOD comparable to quantitative real-time polymerase chain reaction (qPCR). Notably, no cross-reactivity was observed with other common feline pathogens and the consistency of the three methods with qPCR results ranged from 97.22 to 100% in applications of 36 clinical samples. These findings demonstrated that One-tube, two-tube and One-tube-LFS biosensors were capable of rapidly, sensitively, and specifically detecting FPV. The RAA and CRISPR/Cas12a systems were spatially segregated, with the former placed at the bottom and the latter at the cap of the tube. This strategy effectively avoided the cleavage of target DNA and primers by Cas12a during the critical exponential amplification phase of RAA, thereby significantly enhancing the DNA amplification efficiency. The three biosensors could be used for on-site detection in 1 h, and the results could be visualized through fluorescence quenching or LFS. These techniques provide point-of-care testing solutions for clinical diagnosis and rapid screening, especially in resource-limited settings.